Chronic Subdural Hematoma Spontaneous Resolution - Rabelo, Nícollas Nunes; Pereira, Vitor Hugo Honorato; Santos dos Passos, George; Silveira Filho, Luciano José; Cicilini, André Luiz; Rabelo, Neiffer Nunes; Dias Junior, Luiz Antônio Araujo; Pereira, Carlos Umberto; Dias, Luiz Antônio Araujo (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2017)
Introduction Chronic subdural hematoma (CSH) is a hemorrhagic brain injury that persists for more than 21 days after its initial formation. The incidence is predominantly among the elderly population (> 65 years), and varies from 58 to 74/100,000 inhabitants. Spontaneous resolution is considered variable; in the literature series, it is < 1–20% of cases.Objectives To expose the CSH pathophysiological mechanisms of spontaneous resolution and some treatments that lead to hematoma volume reduction.Methods Literature review between 1971 to 2016, using the PubMed, Medline, Embase, Scielo, LILACS and Cochrane databases using key-words, with inclusion and exclusion criteria.Discussion Spontaneous resolution of the CSH pathophysiology is controversial; however, it can be attributed to four basic mechanisms: 1) outer capsule membrane maturation; 2) decreased fibrinolysis; 3) bidirectional flow of blood vessels; and 4) platelet plug. Some drugs, such as mannitol, corticosteroids, tranexamic acid and atorvastatin, contribute to CSH resolution, since they change the capsule membrane permeability, and inhibit the fibrinolytic and inflammatory systems.Conclusion Spontaneous resolution is unpredictable; in some cases, it has a large temporal evolution (of up to 6 years). It occurs in small or laminar collections, asymptomatic or with transient neurological symptoms, and the pathophysiology is still controversial to this day. Therefore, surgical treatment should remain the first option, even though the conservative management is adopted for some patients. Rigorous outpatient and radiological follow-up are recommended.
Keywords: chronic subdural hematoma; spontaneous remission; brain injury